RNAseq, transcriptome analysis and identification of DEGs involved in development and ripening of Fragaria chiloensis fruit - Gaete-Eastman, Carlos; Stappung, Yazmina; Molinett, Sebastián; Urbina, Daniela; Moya-Leon, María Alejandra; Herrera, Raúl (Frontiers in Plant Science, 2022)
Fragaria chiloensis (Chilean strawberry) is a native species that produces fruit with an exotic pinkish color and fruity aroma. It has a non-climacteric pattern of fruit ripening, and it is the mother of the commercial Fragaria x ananassa. The ripening of F. chiloensis fruit seems to be stimulated by ABA and a complete set of genes participate in its softening, color and aroma development. In addition, a set of transcription factors participates in the regulation of the entire process, but few of them have been described. RNA-seq strategy, has contributed, over the last two decades to allow the identification of a high number of genes involved in a biological process. Therefore, RNA-seq was used to identify genes at three fruit development/ripening stages, named C2 (unripe, large green) to C4 (full ripe), in whole fruit and fruit without achenes. A total of 204,754 contigs were assembled considering all samples, obtaining an N50 of 1.125 bp. Differentially expressed genes (DEGs) between two samples were identified obtaining a total of 77,181 DEGs. Transcripts for genes involved in ABA biosynthesis present a high and differential expression during C2, C3 and C4 stages. Besides, contigs corresponding to ABA-receptors which interact into a regulatory network are also differentially expressed. Genes associated to cell wall remodeling were also differentially expressed as well as those involved in the synthesis of flavonoids. A network of interaction was built considering differentially expressed genes for the phenylpropanoid and flavonoid molecular pathway and having FcMYB1as transcription factor regulator. The identification of key genes, could give an option to control ripening of this non-climacteric fruit.